PREPARATION AND CHARACTERIZATION OF TL2BA2CACU2O8 THIN-FILMS BY LASER ABLATION AND THALLIUM DIFFUSION - Liu, R; Shih, W; Scott, K; Edwards, P; Phillips, W; Greer, A (1992)
We report here the growth of Tl2Ba2CaCu 2O8 thin films by a combination of laser ablation and thallium diffusion on [001] MgO substrates. We find that the process configuration and sintering temperatures for thallium diffusion are of paramount importance in achieving single phase thin films. From x-ray diffraction analysis, the films have a highly preferred orientation with the c crystal axis perpendicular to the surface of the substrate. A typical film has a T c(onset) = 120 K, Tc(midpoint) = 115 K, and T c(zero) = 109 K. The critical current density for a film, estimated from hysteresis loop and the Bean Model, is greater than 105 A/cm2 at 5 K in zero applied field.